Driving Global Apparel Consumption: The Impact of Cause Marketing on Indonesian Fashion Purchases: Mendorong Konsumsi Pakaian Global: Dampak Cause Marketing terhadap Pembelian Produk Fashion di Indonesia - Haque, Marissa Grace; Rimadias, Santi (Universitas Muhammadiyah Sidoarjo, 2024)
This study employs a quantitative approach to investigate the role of cause-related marketing (Cr-M) in enhancing purchase intention for Chikigo, a local fashion brand in Indonesia. Utilizing Partial Least Squares (PLS) analysis via Smartpls 3.0 software, data from 64 respondents gathered through online questionnaires were analyzed. The findings reveal a positive impact of attitudes toward cause-related marketing on brand attractiveness, brand image, and purchase intention. Moreover, brand credibility significantly influences attitudes toward cause-related marketing. While brand image positively affects purchase intention, brand attractiveness and credibility do not significantly influence purchase intention for Chikigo's local fashion brand. These results contribute to understanding consumer behavior in the context of cause-related marketing and have implications for marketers seeking to promote local fashion brands in Indonesia.